The Clinical Characteristics of Infertile Women with Premature Ovarian Insufficiency: A Retrospective Analysis (Bangladesh Journal of Obstetrics & Gynaecology, 2022)
Objective: To explore the clinical profile of infertile women with premature ovarian insufficiency, previously termed premature ovarian failure presenting to a public health facility.Materials and methods : A retrospective study was carried out in which the data collected over three years from 2015-2017 in the Gynae Endocrine Clinic of Infertility unit of the Department of Obstetrics & Gynaecology, Bangabandhu Sheikh Mujib Medical University. A total of 36 infertile women diagnosed as premature ovarian insufficiency were included in the study. Detailed data from the records of the clinic regarding symptoms, history related to possible etiology, investigations including endocrine profile and karyotype were included in the analysis. A follow up interview over cell phone was carried out in 2020 to have the information about any pregnancy and compliance with drug over 2- 5 years.Results: A total of 36 women with infertility which were due to premature ovarian insufficiency were included. The mean age was 30.35±5.16 years. Four women were under 25 years and one of them had primary amenorrhoea. Median values with interquartile range of serum FSH, serum AMH and estrogen were 47IU/L ,0.16ng/ml and 22.83pg/ml respectively.Hypoestrogenic symptoms like hot flush and vaginal dryness were present in 50% and 38.9% of the women respectively. While the possible causes of premature ovarian insufficiency were predicted from history, examination and investigations, autoimmune cause was most common (41.7%) followed by genetic/familial causes (25%). Two (5.6%) women conceived spontaneously. None of the women was compliant with the hormone replacement therapy we prescribed.Conclusions: Detailed evaluation with history, examination and investigation for possible causes of premature ovarian insufficiency should be done though the primary concern is infertility. Counseling should emphasize on the need of hormone replacement therapy and the probability, though small, of spontaneous pregnancy.Bangladesh J Obstet Gynaecol, 2020; Vol. 35(2): 90-95